PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN DI PLANET BAN KARAWANG - Ikbal Anggara (Bajang Institute, 2024)
In the era of free market at the moment the consumer is a person or a group of individuals who have an urgent role for the company. Then the auto companies should be able to provide the degree of stratification that meet customer expectations. Based on te research results in partial service quality and customer satisfaction significantly influence customer loyalty thatwas equal to 39.2% for the variable quality of service and the amount of 27.0%to variable customer satisfaction. In multiple regression test variable quality of service and customer satisfaction together (simultaneous) could be explained by 25.0% variable customer loyalty. While the remaining 75.0% off customer loyalty was influenced by other variables that were not known and were examined in this research. Recommendations for improvement based on QFD is the “process of handling customer complaints were handled directly and immediately “as well as the interrelated relationship existing on the dimensions of reliability attributes “Aplication of reliable work culture”, had a relationship with the three attributes of he column Thecnical Recuirements. So that the researcher suggested to PLANET BAN to do periodical evaluation so the attributes appeared analysis of Costumer Requirement Score (CRS) and the the Thechnical Response Score to be managed and supervised in order to become a management priority service to be equipped, repaired, and enhanced continuously